The Effects of Secondary School Accounting Education on University Accounting Performance—A Canadian Experience* - LYNN, BERNADETTE; SHEHATA, MOHAMED; WHITE, LINDA (Contemporary Accounting Research, 1994)
Abstract. This study examined the impact of high school accounting education on students' performance in the first financial accounting course at a Canadian university, specifically the differential impact of different degrees of exposure to high school accounting (i.e., number of courses taken) and the type of courses (i.e., OAC) versus non‐OAC courses) on the students' performance. The results strongly suggest that previous experience in accounting has a significantly positive relationship with students' performance in the first university accounting course. Although the results show that there is a significant positive correlation between performance and the number of accounting courses taken in high school, the results also indicate no significant difference in performance between students who have taken one or two courses. When controlling for the type of courses taken in high school, the results suggest that OAC students perform significantly better than non‐OAC students. The results reported in this study may have important implications for university curricula policy makers. Résumé. Les auteurs examinent l'incidence de la formation en comptabilité des étudiants de niveau collégial sur leur succès dans le premier cours de comptabilité financière qu'ils suivent dans une université canadienne, et plus précisément la variation de cette incidence selon la mesure dans laquelle ils sont exposés à la comptabilité dans leurs études collégiales (en termes de nombre de cours suivis) et la nature des cours qu'ils suivent (selon que ces cours appartiennent ou non à la catégorie des Ontario Academic Courses (OAC)). Les résultats donnent toutes les raisons de croire que l'expérience préalable en comptabilité a une relation positive significative avec le succès des étudiants dans leur premier cours universitaire de comptabilité. Bien que l'étude aboutisse à la conclusion qu'il existe une corrélation positive significative entre le succès et le nombre de cours de comptabilité suivis au niveau collégial, les résultats n'indiquent aucune différence significative dans le succès des étudiants, selon qu'ils ont suivi un ou deux cours. Selon les résultats de l'analyse, les étudiants ayant suivi des cours appartenant à la catégorie des OAC réussissent beaucoup mieux que ceux qui ont suivi des cours n'appartenant pas à cette catégorie. Les constatations des auteurs pourraient avoir des répercussions majeures sur la conception des programmes universitaires.